Myeloid-Derived Suppressor Cells and Therapeutic Strategies in Cancer. (19th May 2015) - Katoh, Hiroshi; Watanabe, Masahiko
Abstract : Development of solid cancer depends on escape from host immunosurveillance. Various types of immune cells contribute to tumor-induced immune suppression, including tumor associated macrophages, regulatory T cells, type 2 NKT cells, and myeloid-derived suppressor cells (MDSCs). Growing body of evidences shows that MDSCs play pivotal roles among these immunosuppressive cells in multiple steps of cancer progression. MDSCs are immature myeloid cells that arise from myeloid progenitor cells and comprise a heterogeneous immune cell population. MDSCs are characterized by the ability to suppress both adaptive and innate immunities mainly through direct inhibition of the cytotoxic functions of T cells and NK cells. In clinical settings, the number of circulating MDSCs is associated with clinical stages and response to treatment in several cancers. Moreover, MDSCs are reported to contribute to chemoresistant phenotype. Collectively, targeting MDSCs could potentially provide a rationale for novel treatment strategies in cancer. This review summarizes recent understandings of MDSCs in cancer and discusses promissing clinical approaches in cancer patients.